Analysis of randomized clinical trials leading to new drug approvals in India and USA - Chawan, Vihang S.; Badwane, Sagar V.; Gawand, Kalpesh V.; Phatak, Abhishek M.; Naik, Madhura S. (International Journal of Clinical Trials, 2016)
Background:To analyse the number of randomized clinical trials and subsequent new drug approvals in India and USA. Methods: Data was collected for completed randomized clinical trials done by multinational in India and USA from www.clinicaltrials.gov during the period from 1/1/2009 to 31/08/2014 and the subsequent new drug approvals from 1/1/2010 to 31/10/2015 for India obtained from Central Drugs Standard Control Organization (CDSCO) (www.cdsco.nic.in.) website and for USA obtained from United States Food and Drug Administration (USFDA) (www.fda.gov) website. Results were measured in terms of percentage of completed randomized clinical trials for investigational medicinal products (IMP) leading to new drugs approvals in India and USA. Results: A total of 163 randomized clinical trials fulfilled the eligibility criteria. Regrouping them for the same sponsor and IMP resulted in a total of 93 randomized clinical trials. In India, 13 drugs (13.93%) were approved by CDSCO, whereas in USA, 35 drugs (37.62%) were approved by USFDA out of a total of 93 randomized clinical trials. High number of randomized clinical trials were conducted for cancer (17.20%) while less number of randomized clinical trials were conducted for gastrointestinal conditions (3.22%). Conclusions: This study revealed that, there exists a wide gap between the new drug approvals permitted by USFDA and CDSCO. Thus there is disparity in the number of clinical trials conducted and market availability of new drugs in India showing that India is lagging behind the USA in approval of new drugs. The regulatory authorities, investigators and institutional review boards should ensure the availability of new drugs in India after they have been researched in the population.